SGLT2 inhibitor downregulates ANGPTL4 to mitigate pathological aging of cardiomyocytes induced by type 2 diabetes - Yun Wen; Xiaofang Zhang; Han Liu; Haowen Ye; Ruxin Wang; Caixia Ma; Tianqi Duo; Jiaxin Wang; Xian Yang; Meixin Yu; Ying Wang; Liangyan Wu; et al. (Cardiovascular Diabetology, 2024)
Abstract Background Senescence is recognized as a principal risk factor for cardiovascular diseases, with a significant association between the senescence of cardiomyocytes and inferior cardiac function. Furthermore, type 2 diabetes exacerbates this aging process. Sodium-glucose co-transporter 2 inhibitor (SGLT2i) has well-established cardiovascular benefits and, in recent years, has been posited to possess anti-aging properties. However, there are no reported data on their improvement of cardiomyocytes function through the alleviation of aging. Consequently, our study aims to investigate the mechanism by which SGLT2i exerts anti-aging and protective effects at the cardiac level through its action on the FOXO1-ANGPTL4 pathway. Methods To elucidate the underlying functions and mechanisms, we established both in vivo and in vitro disease models, utilizing mice with diabetic cardiomyopathy (DCM) induced by type 2 diabetes mellitus (T2DM) through high-fat diet combined with streptozotocin (STZ) administration, and AC16 human cardiomyocyte cell subjected to stimulation with high glucose (HG) and palmitic acid (PA). These models were employed to assess the changes in the senescence phenotype of cardiomyocytes and cardiac function following treatment with SGLT2i. Concurrently, we identified ANGPTL4, a key factor contributing to senescence in DCM, using RNA sequencing (RNA-seq) technology and bioinformatics methods. We further clarified ANGPTL4 role in promoting pathological aging of cardiomyocytes induced by hyperglycemia and hyperlipidemia through knockdown and overexpression of the factor, as well as analyzed the impact of SGLT2i intervention on ANGPTL4 expression. Additionally, we utilized chromatin immunoprecipitation followed by quantitative real-time PCR (ChIP-qPCR) to confirm that FOXO1 is essential for the transcriptional activation of ANGPTL4. Results The therapeutic intervention with SGLT2i alleviated the senescence phenotype in cardiomyocytes of the DCM mouse model constructed by high-fat feeding combined with STZ, as well as in the AC16 model stimulated by HG and PA, while also improving cardiac function in DCM mice. We observed that the knockdown of ANGPTL4, a key senescence-promoting factor in DCM identified through RNA-seq technology and bioinformatics, mitigated the senescence of cardiomyocytes, whereas overexpression of ANGPTL4 exacerbated it. Moreover, SGLT2i improved the senescence phenotype by suppressing the overexpression of ANGPTL4. In fact, we discovered that SGLT2i exert their effects by regulating the upstream transcription factor FOXO1 of ANGPTL4. Under conditions of hyperglycemia and hyperlipidemia, compared to the control group without FOXO1, the overexpression of FOXO1 in conjunction with SGLT2i intervention significantly reduced both ANGPTL4 mRNA and protein levels. This suggests that the FOXO1-ANGPTL4 axis may be a potential target for the cardioprotective effects of SGLT2i. Conclusions Collectively, our study demonstrates that SGLT2i ameliorate the pathological aging of cardiomyocytes induced by a high glucose and high fat metabolic milieu by regulating the interaction between FOXO1 and ANGPTL4, thereby suppressing the transcriptional synthesis of the latter, and consequently restoring cardiac function. Graphical abstract